2019
DOI: 10.7150/thno.29761
|View full text |Cite
|
Sign up to set email alerts
|

ClC-7 Regulates the Pattern and Early Development of Craniofacial Bone and Tooth

Abstract: Human CLCN7 encodes voltage-gated chloride channel 7 (ClC-7); mutations of CLCN7 lead to osteopetrosis which is characterized by increased bone mass and impaired osteoclast function. In our previous clinical practice, we noticed that osteopetrosis patients with CLCN7 mutations had some special deformities in craniofacial morphology and tooth dysplasia. It is unclear whether these phenotypes are the typical features of CLCN7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 64 publications
(70 reference statements)
1
26
0
Order By: Relevance
“…Whole-mount in situ hybridization in zebrafish was performed as previous study 67 , 68 . Digoxigenin-labelled antisense RNA probes were produced with a DIG RNA labeling kit (Roche, #11175025910).…”
Section: Methodsmentioning
confidence: 99%
“…Whole-mount in situ hybridization in zebrafish was performed as previous study 67 , 68 . Digoxigenin-labelled antisense RNA probes were produced with a DIG RNA labeling kit (Roche, #11175025910).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, SB431542 can also induce hiPSCs differentiation into MSCs in a simple one-step and costeffective manner 56,57) . Shi et al reported that SB431542 alone could robust osteogenesis of autologous human gingival mesenchymal stem cells to successfully repair minipig severe maxillofacial bone defects [58][59][60][61] . Here we selected hiPSC-MSCs as the initial seeding cells.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 TGF-β1 and their receptors have been found to be related to zebrafish craniofacial bone and cartilage development. 34 The cartilage development may be affected by indirect regulating function of LTBP1 and TGF-β1. Besides, LTBP1 may directly affect chondrocytes as an important extracellular matrix protein.…”
Section: Discussionmentioning
confidence: 99%